Determinants of private sector investment in a less developed country: A case of the Gambia - Raphael Kolade Ayeni (Cogent Economics & Finance, 2020)
The Gambia as one of the LDCs has made so many efforts to industrialize its economy. The Gambia Investment and Export Promotion Agency, GIEPA, was formed to develop Free Zones in selected locations to enable investors to operate in a more macroeconomic friendly environment. Despite all efforts, the Gambia economy suffers from limited availability of foreign exchange, weak agricultural output, a slowdown in their major investment-tourism, high inflation, a huge fiscal deficit, and a huge domestic debt burden. This study identified the determinants of domestic private investment in the Gambia. The study employed the ARDL Co- integration method to analyze a long-run equilibrium model of private investment. Exchange rate, credit to private sector, external debts, Real Interest Rate, Real Exchange Rate, Inflation, among others were identified as exogenous variables. Findings show that high exchange rate increased the real cost of import especially capital goods thereby making investment very costly. Financing of huge debts also inhibited private investment in the Gambia. Aggregate Demand Condition, Real Interest Rate, Real Exchange Rate, Inflation all performed below expectation. Credit to the private sector has not contributed effectively to boost private investment in the Gambia due to insufficient credit. The study therefore suggests an exchange rate policy that will be favorable to reduce cost of imported capital goods. The Gambia should look inward for the supplying of raw materials locally or promote investment in the areas where the required raw materials are available locally as stated by the comparative advantage theory.
Keywords: E22; 330; ARDL; credit to private sector; external debt; Gambia economy; private investment